Ethnic politics as an eternal clog in the wheels of politics: a Nigerian assessment - Nwauba, Tochukwu; Chieji, Vincent Chukwudi (Penerbit Universiti Kebangsaan Malaysia, 2019)
The thrust of this paper is an examination into an essential and perhaps an overly underplayed character of Nigerian politics. Following a vast multi-cultural diversity crisscrossing Nigeria’s society, ethnic/divisional politics has saddled Nigeria's over 50 years of statehood, dictating and influencing dynamics in and around socio-political and economic spheres. Like in most developing states, this has dramatically undermined Nigeria’s politics overall growth and development, while limiting Nigeria’s potentials and national power. Adopting the Instrumentalist paradigm, this survey finds that although colonial legacies among other structures, entrenched and sustain ethnic politics in Nigeria, on the whole, politicians and personal interests stand as principal exploiters of the ever-growing defect in Nigeria’s polity. Current antecedents show that ethnic politics like in the past only holds more grave and dangerous spirals of conflict, political crises etc., of great magnitude going forward. Thus, robust and bold moves toward mitigating ethnic politics in Nigeria is of critical importance. Given this reality, this piece advocates more sincerity and commitment from all stakeholders: the government, individuals and the civil society. Also, qualitative investments must be made into political socialisation/education; while strengthening the institutions and activities that emphasise unity across the country.